2020
DOI: 10.1155/2020/8826787
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regional Spontaneous Neural Activity in Nonarteritic Anterior Ischemic Optic Neuropathy: A Resting-State Functional MRI Study

Abstract: Objective. To explore altered regional neuronal activity in patients with nonarteritic anterior ischemic optic neuropathy (NAION) and its correlation with clinical performances using the regional homogeneity (ReHo) method, which is based on resting-state functional magnetic resonance imaging (fMRI). Method. Thirty-one patients with NAION (20 males, 11 females) and 31 age- and sex-matched normal controls (NCs) (20 males, 11 females) were enrolled in the study. All patients underwent ophthalmic examination, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Japee et al [ 52 ] demonstrated that this function may be conducive to remedying the effect of lesions in areas of the cerebrum. Previous studies [ 33 , 53 ] have indicated that there are decreased ReHo and degree centrality values of MFG_R in DON patients. ReHo was used to evaluate local synchronization of adjacent voxels in the whole cerebrum at rest [ 54 ], and degree centrality was used to observe the connectivity of cerebrum networks at the voxel level [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Japee et al [ 52 ] demonstrated that this function may be conducive to remedying the effect of lesions in areas of the cerebrum. Previous studies [ 33 , 53 ] have indicated that there are decreased ReHo and degree centrality values of MFG_R in DON patients. ReHo was used to evaluate local synchronization of adjacent voxels in the whole cerebrum at rest [ 54 ], and degree centrality was used to observe the connectivity of cerebrum networks at the voxel level [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Japee et al [52] demonstrated that this function may be conducive to remedying the effect of lesions in areas of the cerebrum. Previous studies [33,53] have indicated that there are decreased ReHo and degree ReHo was used to evaluate local synchronization of adjacent voxels in the whole cerebrum at rest [54], and degree centrality was used to observe the connectivity of cerebrum networks at the voxel level [55]. However, dALFF as an extension of rs-fMRI can better reflect the dynamic electrical activity of the cerebrum in diseases, especially applied in DR [28], consciousness [20], anxiety [56], and depression [57].…”
Section: Discussionmentioning
confidence: 99%
“…The regional homogeneity (ReHo) method is a resting pattern functional magnetic resonance surveying method that has been used to assess lesions of the cerebrum ( Guo et al, 2020 ). The ReHo method can measure the similarity of a time series of specific voxels and their nearest neighbors ( Ding et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In technical BOLD studies, it was found to be useful for demonstrating abnormal cortical structure and function in patients with nonarterial anterior ischemic optic neuropathy (NAION). In addition to being noninvasive, fMRI also has advantages of high spatial resolution and recognition of neuronal activity[ 7 ]. fMRI has been applied to study cortical reorganization after NAION[ 8 ], and the results showed that neuronal activity in the occipital visual area plays an vital role in visual acuity, while a complete visual pathway depends on the normal activation of neurons in the visual cortex.…”
Section: Introductionmentioning
confidence: 99%